The Effects of Investment Bank Rankings: Evidence from M&A League Tables - Derrien, François; Dessaint, Olivier (Review of Finance, 2018)
Abstract This paper explores how league tables, which are rankings based on market shares, influence the mergers and acquisitions market. A bank’s league table rank predicts its future deal flow, above and beyond other determinants. This creates incentives for banks to manage their league table ranks. League table management tools include selling fairness opinions (FOs) and reducing fees. Banks use such tools mostly when their incentives to do so are high: when a transaction affects their league table position or when they lost ranks in recent league tables. League table management seems to affect the quality of FOs.